Service Compatibility (Servicom) and Service Delivery in the Nigerian Police Force - S. Olowe, Temitope; A. Nkwuagba; Adeola A. Ayodele, John (British Journal of Marketing Studies, 2018)
This study centers on service compatibility (SEVICOM) and service delivery in the Nigerian Police Force (NPF). Empirical studies on service delivery in the Nigerian civil authority sector 3124are very scanty. The broad objective of this study is to investigate empirically the effect of service compatibility (SERVICOM) on the quality of service delivery in the NPF. In order to achieve this objective, survey design was adopted and the population of study comprises the police officers in the Ekiti state police command and the consumers of police service in Ekiti state, Nigeria. Taro Yamane’s formula was used to determine the sample sizes of both the police personnel and the consumers of police service in Ekiti State. Stratified random sampling and convenience sampling were used as the sampling methods for the police personnel and the consumers of police service respectively. Questionnaire was adopted and the reliability was tested using Cronbach’s alpha coefficient. Descriptive statistics was used to analyze the research questions while One-way ANOVA and simple linear regression were used to test the hypotheses. It was found that the introduction of SERVICOM into the NPF has no significant effect on the quality of the service delivery in the NPF, both service timeliness and service professionalism has positive effect on NPF service delivery though not statistically significant. It was concluded that this study has provided empirical evidences that SERVICOM introduction has not improve timeliness and professionalism of service in the NPF. We recommend that the NPF should set machinery in motion to ensure full implementation of SERVICOM in order to improve the quality of service delivery in the Nigerian Police Force.